2023
DOI: 10.1007/s40496-023-00339-y
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Health and Psychiatric Disorders

Abstract: Purpose of Review People with mental illness are vulnerable to periodontal diseases. Explanations include the direct effects of the psychiatric illness, side effects of psychotropic medication, lifestyle (e.g., alcohol, tobacco, and other substance use), shared risk factors, and difficulties with activities of daily living and access to dental care. Recent Findings Latest findings confirm the bi-directional relationship between periodontal disease and both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…It has been reported that worldwide, 5-50% of the population suffering from periodontitis eventually lose their teeth [3][4][5]. Some of the behavioral factors that can cause periodontal diseases include smoking [6][7][8], chronic alcohol consumption [9,10], nutritional deficiency [11,12], psychological issues [13,14], and systemic diseases [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that worldwide, 5-50% of the population suffering from periodontitis eventually lose their teeth [3][4][5]. Some of the behavioral factors that can cause periodontal diseases include smoking [6][7][8], chronic alcohol consumption [9,10], nutritional deficiency [11,12], psychological issues [13,14], and systemic diseases [15][16][17].…”
Section: Introductionmentioning
confidence: 99%